Flipped Classroom: Theoretical Reflections for Implementation in Social Studies - Gamboa Fallas, Marisol (2024)
This article presents a conceptual and procedural approach to the didactic strategy of flipped classroom applied to the teaching and learning processes of Social Studies. The article analyzes the concept of flipped classroom, its relevance to Social Studies Didactics and the considerations that may apply. As well as an attempt to determine possibilities and challenges when executing it in the development of the contents of this subject. The article concludes that flipped classroom is a technique able to transform the traditional role of the participants in the educational process of Social Studies. This technique fosters a greater interest for students in the construction of their knowledge, also encourages spaces for reflection, analysis and autonomous work. Lastly, flipped classroom is an ideal technique to encourage active methods and better time management that would enable an increase in academic quality.